2015
DOI: 10.1108/jes-08-2013-0118
|View full text |Cite
|
Sign up to set email alerts
|

Financial liberalization and economic growth

Abstract: Purpose – The purpose of this paper is to ascertain whether countries benefit from capital account liberalization in more democratic contexts. Design/methodology/approach – The authors used the follow methodologies in this paper: Pooled OLS, panel data with fixed effects and generalized method of moments. The empirical exercises were conducted for both a large sample and a smaller group of developing countries. Given the characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…their credit, loans, profit ideas, and competences (Osei-Tutu and Weill, 2023). The substantive implication: the higher is the level of democracy, the more favorable, in principle, is the business, economic and financial climate (Lopes and de Jesus, 2015; Delis et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…their credit, loans, profit ideas, and competences (Osei-Tutu and Weill, 2023). The substantive implication: the higher is the level of democracy, the more favorable, in principle, is the business, economic and financial climate (Lopes and de Jesus, 2015; Delis et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Akıncı et al (2015) have revealed in their studies that financial freedom has positive effects on economic growth. The effects of financial freedom on economic growth has been researched by Lopes and Jesus (2015). It is observed that the financial freedom positively affects economic growth only in countries with a high democratic system.…”
Section: Introductionmentioning
confidence: 99%
“…Akıncı et al (2015) have revealed in their studies that financial freedom has positive effects on economic growth. The effects of financial freedom on economic growth has been researched by Lopes and Jesus (2015). It is observed that the financial freedom positively affects economic growth only in countries with a high democratic system.…”
Section: Introductionmentioning
confidence: 99%